Comparison of branch and distally focused main renal artery denervation using two different radio-frequency systems in a porcine model. (15th August 2017) - Mahfoud, Felix; Pipenhagen, Catherine A.; Boyce Moon, L.; Ewen, Sebastian; Kulenthiran, Saarraaken; Fish, Jeffrey M.; Jensen, James A.; Virmani, Renu; Joner, Michael; Yahagi, Kazuyuki; Tsioufis, Costas; Böhm, Michael
Abstract: Objectives: Anatomic placement of lesions may impact efficacy of radio-frequency (RF) catheter renal denervation (RDN). However, it is unclear if it is necessary to perform treatments post bifurcation with systems that may provide deeper penetration to achieve successful RDN. Methods: Sixteen domestic swine ( n = 16) were randomly assigned to 4 groups: 1) 8 lesions created in the branch arteries using the Spyral catheter (SP8); 2) 8 lesions created in the branch arteries plus 4 lesions created in the main artery using the SP catheter (SP12); 3) 8 lesions created in the main artery using the EnligHTN catheter with the distal position as close as possible to the bifurcation (EN8); and 4) 12 lesions created in the main artery using the EN catheter with the distal position as close as possible to the bifurcation (EN12). Results: Each arm showed statistically significant changes in kidney norepinephrine (NE, ng/g) between treated kidneys vs. untreated contralateral control. There were no statistically significant differences in tissue NE% reductions across each arm based on catheter, anatomic location, & number of lesions ( p = 0.563):EN8 –74 ± 34%, EN12 –95 ± 3%, SP8 –76 ± 16%, SP12 –82 ± 17% ( p = 0.496). A total of 46 lesions were measured for lesion depth: EN main (3.3 ± 2.8 mm) vs. SP branch (2.0 ± 1.0 mm, p = 0.039), SP main (2.9 ± 1.6 mm) vs. SP branch ( p = 0.052), and EN main vs. SP main ( p = 0.337). Conclusions: Distally-focused main renal artery treatment using the EN system appears to be equally efficacious in reducing tissue NE levels compared with SP treatment in the branches plus main renal arteries, advocating for device-specific procedure execution.